BOOK REVIEWS: Isabelle C. Druc. Portable Digital Microscope - Atlas of Ceramic pastes: Components, Texture and Technology. Deep University Press, Blue Mounds, Wisconsin, 2015, 120 pages, 140 + colour photographs. (2015) - Ixer, Rob
No abstract available